Environmental efficiency analysis and estimation of CO2 abatement costs in dairy cattle farms in Umbria (Italy): A SBM-DEA model with undesirable output. (1st October 2018) - Cecchini, Lucio; Venanzi, Sonia; Pierri, Antonio; Chiorri, Massimo
Abstract: Livestock activity is one of the most contributors to climate-change emissions in the agriculture sector. European environmental policies face with the challenge of increasing farmers economic gain not conflicting with environmental aim at the same time, to meet targets for reducing greenhouse gas emissions (GHG). The paper aims to contribute to the discussion on CO2 emission mitigation by providing efficiency performance measures in the presence of joint production of milk and GHG emissions. A Slacks-Based Measure-Data Envelopment Analysis (SBM-DEA) with undesirable output was adopted and integrated with Life Cycle Analysis (LCA) results from 10 dairy cattle farms in Umbria (Italy) to estimate their environmental efficiency and emission reduction potential. In addition, the dual model of the SBM-DEA was used to quantify the marginal CO2 reduction costs. Four farms resulted in no CO2 -eq emission efficient, with a reduction potential ranging from 45.7% to 26.3% of CO2 -eq. An average abatement cost of € 243.08 in terms of lower milk production per ton of CO2 -eq reduced, was estimated for the whole sample. A positive relationship between marginal abatement costs and CO2 -eq efficiency scores was estimated. Marginal abatement costs knowledge could allow assessing the economic impacts of different farms strategies aimed at reducing polluting emissions, as well as the introduction of incentive mechanisms by public decision makers. Highlights: The research focuses on cattle dairy sector in Umbria region (Italy). The SBM-DEA model is applied to assess the environmental efficiency. Shadow prices of GHG emission are estimated. High reduction potential of CO2 emissions are quantified. Marginal abatement costs and CO2 -eq efficiency show a positive relationship.